PENGETAHUAN PERTOLONGAN PERTAMA PADA PERDARAHAN LUAR VOLUNTEER FIRE BRIGADE DI DATARAN TINGGI PT FREEPORT INDONESIA - Andre Nugroho Tandi; Untung Sudharmono (Jurnal Kesehatan, 2022)
Workplace is a place that has a working workforce and has a risk of occupational hazards or risks creating work accidents. One of the emergencies that are often found is bleeding. The purpose of first aid outside bleeding is to prevent excess blood loss, maintain the victim's life, reduce pain, discomfort, excessive anxiety, and maintain the victim's condition remain stable. The management of external bleeding cannot be separated from knowledge of the actions performed. The method used in this study is quantitative descriptive with pre-experimental design type one group pretest-posttest. The population in this study is volunteer fire bridgade in the Highlands of PT Freeport Indonesia. Sampling technique with probability sampling technique with sample criteria is volunteer fire bridgade in the Highlands of PT Freeport Indonesia. This study obtained the results of the paired T-test with a significance value of 0,000 smaller than 0.05 (0.000 < 0.05) so that it can be concluded that there is a significant difference in the level of pre-test and post-test knowledge after being given health education. The increase in respondents' knowledge can be seen from the increase in the average value of knowledge from 41,759 to 60,992.